PENGARUH PROGRAM PELATIHAN, PENGEMBANGAN KARYAWAN DAN BUDAYA ORGANISASI TERHADAP KOMPETENSI KARYAWAN PT. WASKITA KARYA (PERSERO) Tbk. CABANG PEKANBARU - Dina Novita; Marzolina Marzolina; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Waskira Karya (Persero) Tbk. Cabang Pekanbaru with the aim to explain the variable training program, employee development and organizational culture in simultaneous and parcial to employee competency at PT. Waskira Karya (Persero) Tbk. Cabang Pekanbaru.This research used pimary data namely data were obtained from interviews and administration of the questionnaire to all employees at PT. Waskira Karya (Persero) Tbk. Cabang Pekanbaru. Secondary data relating to the object and organizational structure. Population in this research were all employees totaling 40 people and sampled. Methods of analysis used in this research is the method of multiple linear regression.Of the results of the testing that has been done, simultaneous regression test (uji-F) suggests that training program, employee development and organizational culture variables simultaneously significant effect on employe competency. Of the partial test (uji-t) result indicate that the variables of training program, employee development and organizaional culture are partially significant efect on employee competency. Results of caculation coefficient of determination is equal to 0,610 which mean, training program, employee development variables and organizational culture jointly influenced by other variables not examined in this research.Keywords : Training, employee, development, organizational culture, and competency